Analisis Dampak Penerapan Kebijakan Pembatasan Sosial Berskala Besar Terhadap Tenaga Kerja Di Kabupaten Karawang - Revi Revi; Helvis Helvis; Markoni Markoni (Jurnal Syntax Transformation, 2021)
The spread of the corona virus covid-19 (Covid-19) throughout the world which causes a high death toll has forced the government to take steps to prevent the spread of the COVID-19 virus more broadly, so that a Large-Scale Social Restriction (PSBB) policy was issued. broad impact for all groups, such as restrictions on business activities, as a result a number of companies experienced a decrease in production output and a decrease in income, but on the other hand expenses were increasing apart from operational costs as well as unexpected costs in the form of costs for implementing health protocols such as purchasing masks, hand soap and alcohol (hand sanitizer). So that the company faces the dilemma of having to fulfill its obligations to the workforce but on the other hand must maintain its business so as not to close, then a number of policies in the field of manpower are taken in the form of implementing wage cuts and layoffs. The Constitution protects the rights of workers as outlined in the Manpower Act. The research problem is whether companies affected by the implementation of the PSBB can cut wages and/or lay off their workers? And how is the legal protection? The qualitative research method, with the approach it uses is juridical normative, looking for problems raised from reading materials sourced from library studies. The result of the research is that the deduction of workers' wages because the company loses money due to the implementation of the PSBB is not based on law and causes industrial relations disputes, namely rights disputes. Regarding layoffs, there are humanitarian issues that must be prioritized according to a very clear order contained in Law no. 13 of 2003 concerning Manpower, which states that the government and employers with all efforts must as much as possible avoid the occurrence of layoffs. Suggestions are that companies and workers communicate in order to maintain harmonious working relations, and follow the steps determined by SE-907/MEN/PHIPPHI/X/2004 and the Constitutional Court's Decision No. 19/PUU-IX/2011 before doing layoffs. Also, the government and the company provide entrepreneurship training prior to layoffs